Transcriptome based identification and validation of heat stress transcription factors in wheat progenitor species Aegilops speltoides - Sushmita Seni (Nature Portfolio, 2021)
Abstract Wheat, one of the major cereal crops worldwide, get adversely affected by rising global temperature. We have identified the diploid B genome progenitor of wheat, Aegilops speltoides (SS), as a potential donor for heat stress tolerance. Therefore, the present work was planned to study the total transcriptome profile of heat stress-tolerant Ae. speltoides accession pau3809 (AS3809) and compare with that of tetraploid and hexaploid wheat cultivars PDW274 and PBW725, respectively. The comparative transcriptome was utilized to identify and validate heat stress transcription factors (HSFs), the key genes involved in imparting heat stress tolerance. Transcriptome analysis led to the identification of a total of 74 K, 68 K, and 76 K genes in AS3809, PDW274, and PBW725, respectively. There was a high uniformity of GO profiles under the biological, molecular, and cellular functions across the three wheat transcriptomes, suggesting the conservation of gene function. Twelve HSFs having the highest FPKM value were identified in the AS3809 transcriptome data, while six of these HSFs namely HSFA3, HSFA5, HSFA9, HSFB2a, HSFB2b, and HSFC1b, were validated with qRT PCR. These six HSFs were identified as an important component of thermotolerance in AS3809 as evident from their comparative higher expression under heat stress.